SEA NAVIGATION COMMUNICATION: REALIZATION AND LEXICO-GRAMMATICAL FEATURES - Wardani, Henny Wahyu (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2009)
Communication makes use of language with its inherent features which are determined by its contents: context of culture and context of situation. Maritime communication falls within closed register which provides fixed realization which is ritualized having no other variation. The ritual constraints can be seen in its unfolding sequence of communication: Summon-response; turn-over signal and useof explisit message markers., ÃÂ Key words: contex of situation, closed register, ritual constraints, Message-Markers.